Pseudomonas aeruginosa Septic Arthritis and Osteomyelitis after Closed Reduction and Percutaneous Pinning of a Supracondylar Humerus Fracture: A Case Report and Review of the Literature - Adam M. Wegner; John C. Wuellner; Brian M. Haus (Case Reports in Orthopedics)
Infectious complications of closed reduction and percutaneous pinning of supracondylar humerus fractures are exceedingly rare. Although postoperative Pseudomonas infection is a feared complication associated with noncompliance and a wet cast, there are no reports in the literature of this occurring. We present the devastating complication of a pediatric patient who developed Pseudomonas aeruginosa subperiosteal abscess, osteomyelitis, and elbow septic arthritis after presenting to the clinic multiple times with a wet cast after closed reduction and percutaneous pinning of a supracondylar humerus fracture. We describe the treatment course for this patient, followed by the sequelae of posterolateral rotary instability. This case not only confirms that patients can get Pseudomonas infections if they get their cast wet but also stresses the importance of patient communication and compliance in preventing unfortunate complications.